Percepções de enfermeiras sobre o coaching como ferramenta de desenvolvimento de competências gerenciais em um hospital universitário - FONTES, Victória Malcher Silva (2019)
Considering the research problem: can coaching contribute to the managerial skills development of nurse managers in a university hospital? The purpose of this study was to analyze the perception of nurse managers at a university hospital in the Northern region of Brazil about the development of management skills through coaching. This is a descriptive and analytical study of a qualitative nature. Eight nurses were interviewed in leadership positions, and they experienced the coaching process provided in their work environment by an extension project. The interview was based on the participants' perception of the path that had taken place since the beginning of each process, but some specific questions could not be left unanswered, so a semi-structured interview script was developed, which contained 4 questions. As a result of this study, the participating nurses reported being able to perceive themselves within their work environment, reflect on their ideas, modify their behaviors, position themselves in front of issues in the workplace, and feel stronger to deal with difficulties. Participants also showed benefits in personal life, from self-discovery, understanding their goals, prioritization and focus on desired goals. It is concluded that the coaching tool is effective in developing managerial skills necessary for the leading nurse, and in both the professional and personal spheres, coaching has brought about encouragement, self-confidence, self-motivation and action alternatives to deal with unfavorable situations.